Lobular intraepithelial neoplasia: Outcomes and optimal management. Issue 12 (3rd December 2020) - Boland, Patrick A.; Dunne, Emma C.; Kovanaite, Akvile; Stokes, Maurice; Kell, Malcolm R.; Barry, John Mitchel; Kennedy, Margaret; Flanagan, Fidelma; Walsh, Siun M.
Abstract: Introduction: Lobular neoplasia is a term encompassing both atypical lobular hyperplasia and lobular carcinoma in situ. These pathological findings are of uncertain malignant potential and predispose to a higher lifetime risk of breast cancer. Debate surrounds the management of such lesions, with the rationale for diagnostic excision based on the possibility of upgrading to malignancy. In this study, we report the upgrade rate of these lesions and risk of subsequent development of breast cancer. Methods: This is a retrospective review of a prospectively maintained data base of all biopsies of breast screening‐detected abnormalities in a single Irish breast‐screening unit. We included all patients with lobular neoplasia on core needle biopsy who underwent diagnostic excision from 2005 to 2012. We excluded those who had concurrent high‐risk lesions on biopsy. End points included upgrade rate and subsequent diagnosis of malignancy on follow‐up. Results: During the study period, 66 patients met criteria for inclusion, with a mean age of 53.74 years. Upgrade rate following excision was 13.64% (n = 9/66). Of those not upgraded, 7.02% (n = 4/57) were subsequently diagnosed with malignancy. Median time to diagnosis was 59.61 months (range = 10.5‐124.4). Conclusion: There is a significant rate of upgrade following diagnostic excision of lobular neoplasia, supporting the practice of diagnostic excision. There is an increased lifetime risk of breast cancer for women with a diagnosis of lobular neoplasia, with many of these cancers occurring outside the standard five‐year monitoring period, suggesting a potential benefit in extending surveillance.